Nicotine Dependence, Readiness to Change Behavior among Tobacco Users Attending Tertiary Care Hospital's De-Addiction Clinic in Uttarakhand - Rajesh Kumar; Hoineiting R. Haokip; Kalpana Beniwal; Yogesh Bahurupi (Indian Journal of Psychiatric Nursing)
Introduction: Tobacco use is a significant cause of many respiratory diseases and preventable deaths in India. The crunch of information on the magnitude of the tobacco use problem unable to planned and implement tobacco cessation programs in the Himalayan region. This study aims to determine nicotine dependence and readiness to change behavior in tobacco users attending a tertiary care teaching hospital's de-addiction clinic. Materials and Methods: This descriptive study purposively included 120 tobacco users over 6 months in a public hospital's de-addiction clinic, North India. A structured personal and clinical profile sheet, the Fagerstrom Test for Nicotine Dependence-Revised Version-smokable and smokeless), and Readiness to Change Questionnaire (RCQ) were used to collect information. Descriptive and inferential statistics were used to generate the findings. Results: The mean age of tobacco initiation was 20.69 (±6.12) years in the study population, with a median ofthree quit attempts (median: 3; interquartile range: 2–5). Nearly 55.8% and 18.3% of participants were using smokable and smokeless tobacco, respectively. Bidi was the most preferred (75.8%) form of smokable tobacco among study participants. The majority of participants were in the category of high nicotine dependence (76.6%) as per the FTND scale and were in the contemplation phase (55%), whereas 45% of the users found it in the action stage of quitting tobacco. Conclusions: The majority of the participants were in the high nicotine dependence stage. However, readiness to change behavior to quit or reduce tobacco use is noteworthy, emphasizing need-based intervention and assisted follow-up programs to tobacco users in the outpatients.